Evaluación de presencia de nitrógeno (N) y fósforo (P) en el agua de Escorrentía en cultivos de papa. (2017)
In Colombia, the vertimientos product of agroindustrial activities are currently governed by resolution 631 of 2015, in which, in the case of dumping from the agroindustry, nitrogen (N) and phosphorus (P), do not have a maximum limit permissible in the occasional discharges in wastewater, for that case it is only considered a corresponding analysis and report. Given the absence of regulations in Colombia, the existing standards were consulted other countries and entities related to water quality, discharges made to bodies of surface water and / or sewage systems, taking as reference the nitrogen and total phosphorus parameters. For the present study a total of eight samples were made in a potato culture located in the municipality of Ventaquemada belonging to the department of Boyacá, in order to evaluate the presence of total nitrogen (N) and phosphorus (P) in the runoff water from the crop and estimate the corresponding contaminant loads, due to the fact that these elements represent a pollution factor in bodies of surface water. In the case of the studied crop, the contamination of an existing birth is presented, which is irrigated during the summer season or when there are no rain to guarantee it. The nitrogen and phosphorus contents were determined through the macro methods - Kjeldahl, distillation and volumetry, SM 4500-NOrg B and SM 4500-NH3 B, C and the method of acid digestion - ascorbic acid SM 4500 - P B, E respectively. The flow of runoff was obtained through the rational method, taking the intensity variable of rain directly in the field, once the flow was obtained, the respective pollutant loads, the results were compared with the limits set out in the consulted regulations.